Former Yugoslav Republic of Macedonia : Staff Report for the 2014 Article IV Consultation and Third Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2014)
Growth accelerated to 3.1 percent in 2013, driven by a positive net exports contribution. The broad policy direction is supportive of near term macroeconomic stability. The key challenge is to transition from stability into an acceleration of medium term growth. Uncertainty with respect to EU accession remains, and weighs on longer term prospects.